Duplication of inferior vena cava-a rare case report - Abdulrazzaq, Saad Mohammed; Nafie, Emad M.; A. Jabir, Ghassan (International Journal of Innovative Research in Medical Science, 2020)
The inferior vena cava (IVC) is the biggest vein in the human being that started as the result of the union of the right and left common iliac veins at the level of the fifth lumber vertebra. IVC develops as part of the embryonic venous system which is divided into vitelline, umbilical and cardinal system at the beginning of the 5th week. Double IVC incidence ranges between 0.2% -3%. The variation was detected through dissecting a cadaver inthe Faculty of Medicine, International Islamic University Malaysia. We report a left sided IVC accompanied side by side to the normal right one. They joined together by a connecting venous anastomosis at the level of first lumbar vertebra. Double IVC can prolong smoothly without any consequences and may be discovered incidentally by radio-graphical studies, but in some conditions like retroperitoneal surgery, vascular interventional procedures, the study of the anatomy of these variations is of crucial importance.